MAKNA DI BALIK KEINDAHAN RAGAM HIAS DAN INSKRIPSI MAKAM DI SITUS DEA DAENG LITA KABUPATEN BULUKUMBA - Makmur (Badan Riset dan Inovasi Nasional, 2017)
Ornament is basically an element deliberately presented to beautify empty spaces on an object or item which then turns into an artificial yet interesting and beautiful artwork. The tomb ornaments in the archipelago show a mixture of Islamic calligraphy and local culture, in the form of gunungan (Meru) and floral ornaments. This study aims to reveal the Islamic culture in the past through a research on the tomb ornaments and inscriptions. Field observation technique and analysis on multiple forms, functions, and meanings of the ornaments and inscriptions were applied in this research to give a more well-defined image about the Islamic culture and teachings integrated with the local culture. Dea Daeng Lita tomb complex has gunungan (Meru) with vine- like ornaments combined with menhir gravestones and dzikr inscriptions. The combination is a reflection of sufism that also shows harmonization of Islam and local culture that established the civilization in Bulukumba. Ragam hias makam di Nusantara memperlihatkan percampuran, kaligrafi yang dibawah Islam dengan unsur budaya lokal pada pemberian gunungan (meru) dan ragam hias floralistik di makam. Penelitian ini, bertujuan mengungkap kebudayaan Islam pada masa lampau melalui ragam hias dan inskripsi makam. Agar dapat memberikan gambaran, bagaimana kebudayaan dan ajaran Islam terintegrasi dan menyatu kedalam budaya lokal masyarakat. Dalam pencapaiannya digunakan teknik observasi dan analisis dari segi keanekaragaman bentuk, fungsi serta makna ragam hias dan inskripsi. Di kompleks Makam Dea Daeng Lita memperlihatkan paduan jirat gunungan yang terbentuk dari ragam hias sulur-sulur dengan nisan menhir serta inskripsi lafadz zikir dan ketahuidan sebagai refleksi ajaran tasawuf mengambarkan harmonisasi ajaran Islam dengan kebudayaan lokal dalam membentuk peradaban di Kabupaten Bulukumba.